Thermal Performance on Unglazed Photovoltaic Thermal Polymer Collector - Mohd Rosli, Mohd Afzanizam; Mat, Sohif; Sopian, Kamaruzzaman; Sulaiman, M. Yusof; Salleh, Elias @ Ilias; Sharif, Mohd Khairul Anuar (scientific.net, 2014)
In this study, the thermal efficiency of a polymer collector with unglazed photovoltaic thermal (PVT) system was determined. Overall heat loss was estimated using the heat energy balance method. Based on the analysis, the heat removal factor of the PVT system was found to be 0.55. The thermal performance of the system was 47% during the zero reduce temperature. The unglazed PVT polymer collector could replace the conventional PVT collector, which encountered problems such as high cost, weighting issues, and corrosion.